The offences which are considered as the legal actions in the Kingdom under the Thai Criminal Code - เจ๊ะหะ มุฮำหมัดซากี (Al-HIKMAH Journal, 2018)
Taking into account the facts of the place where the offense has occurred in order to enforce criminal laws which aim at to punish offenders can be divided into two cases. Firstly, the criminal offenses are directly occurred in Kingdom and secondly criminal offenses which are considered by the law as if they are committed in the Kingdom. This article will highlight the second case and the study revealed that the criminal offenses shall be deemed guilty in the kingdom on five cases. The first case is the offenses which are committed on ship or aircraft registered in Thailand. The second case is the offenses which are partly committed in the Kingdom. The third case is the offenses which their results are occurred in the Kingdom. The fourth case is the offenses which were prepared or attempted outside the Kingdom. The final case is the offenses in which the conspiracy, the commanders or the supporters are from outside kingdom.